Comparative efficacy and safety of antidiabetic drug regimens added to stable and inadequate metformin and thiazolidinedione therapy in type 2 diabetes. Issue 11 (28th July 2015) - Saulsberry, W. J.; Coleman, C. I.; Mearns, E. S.; Zaccaro, E.; Doleh, Y.; Sobieraj, D. M.
Summary Aims Determine the efficacy and safety of antidiabetic agents added‐on to metformin and a thiazolidinedione (TZD) in patients with inadequately controlled type 2 diabetes (T2D). Methods MEDLINE and CENTRAL were searched for randomised controlled trials (RCTs) evaluating the addition of an antidiabetic agent in patients with T2D inadequately controlled on stable, optimised metformin and TZD therapy (≥ 1500 mg metformin and ≥ 50% maximum TZD dose for ≥ 4 weeks). Frequentist network meta‐analysis was performed on identified studies. Results Eleven RCTs evaluating dipeptidyl peptidase‐4 inhibitors (linagliptin, sitagliptin), sulfonylureas (SUs) (glibenclamide, glimepiride), glucagon‐like peptide‐1 (GLP‐1) analogues (exenatide, liraglutide, dulaglutide, taspoglutide) and sodium‐glucose cotransporter2 (SGLT2) inhibitors (canagliflozin, empagliflozin) were identified. The mean reduction in HbA1c from baseline was significant for all agents (range, 0.55–1.17%) vs. placebo. SUs were associated with weight gain (range, 3.31–7.29 kg), while weight loss was seen with all GLP‐1 analogues (range, 1.53–2.20 kg) and SGLT2 inhibitors (range, 2.08–2.95 kg) vs. placebo. Relative risk of hypoglycaemia was increased with dulaglutide, exenatide and glimepiride vs. placebo (RR range, 2.65–6.17); and trended higher with all other agents except linagliptin. GLP‐1 analogues and canagliflozin reduced systolic blood pressure vs. placebo (range, 2.39–5.05 mmHg). No agent with available data increased the risk of urinary or genital tract infection vs. placebo. Conclusion When added to stable, optimised metformin and TZD, all evaluated antidiabetic agents reduced HbA1c; albeit not to the same degree. Moreover, agents differed in their effects on body weight, hypoglycaemia and systolic blood pressure.